Assessment of Routine Immunization Program at Selected Urban Health Centres in Ahmedabad, Gujarat, India - Jinalben Nogas; Karankumar Desai; Nandan Shah; Mitesh Patel; Shivam Chauhan; Bhavesh Gelot (Indian Association of Preventive and Social Medicine, 2024)
Introduction: Urban Health Centre is a key place for implementing Routine Immunization program and vaccine storage. The present study evaluated Cold Chain Point (CCP) and logistics related to routine immunization at selected Urban Health Centers (UHCs) in Ahmedabad. Objective: 1. To evaluate the cold chain infrastructure and logistics supporting routine immunization programs at UHC with a focus on assessing the quality and reliability of vaccine storage and handling practices. 2. To assess the knowledge about cold chain among the Vaccine Cold Chain Handlers (VCCHS). Method: In this cross-sectional study, one UHC from each of the seven zones of Ahmedabad city was randomly selected for assessment of Cold Chain management. Knowledge of VCCHs at each UHCs was assessed using semi-structured questionnaire. Analysis was done using Microsoft excel 2019. Results: It was observed that all UHCs were having session plans and logistics estimation. Around 28.5% UHCs were having lack of essential tools, such as Drop Out charts and maps of their catchment areas. Open vials were found without dates and times labelled in 43% of UHCs, and in one UHC, a vaccine vial was found beyond its usable Vaccine vial Monitor (VVM) stage. All the medical officers utilize various strategies to create awareness, with the majority (86%) using interpersonal communication. All Health Care Providers stated Socio-cultural beliefs and fear of side effects as reason for non-utilization of services. Only 42% of Vaccine Cold Chain Handlers (VCCHs) demonstrated complete knowledge about live vaccines. Conclusion: The study highlights certain issues at UHC like maintenance of drop out chart, map of catchment area, training of medical officers on module of immunization, ice-packs arrangement in Deep Freeze, no knowledge of VCCHs about shake test, which indicates lack of efficiency of VCCHs and need of their training.